Effects of austenitic stainless steel tube and tubesheet hole dimensional deviations on the hydraulic expansion pressure. (February 2016) - Sui, Rongjuan; Wang, Weiqiang; Liu, Yan; Qu, Yanpeng
Abstract: The minimum hydraulic expansion pressure for the tube and tubesheet hole is calculated using the common theoretical formula and the finite element method. The effects of the tube and tubesheet hole dimensional deviations on the minimum hydraulic expansion pressure are analyzed. The minimum hydraulic expansion pressure obtained from the theoretical formula cannot guarantee a fit between the tube and tubesheet hole because the effects of dimensional deviations are not taken into account. Even if the dimensional deviations are taken into the formula, the correct pressure values cannot be obtained. Finite element analysis show that the deviations of the tubesheet hole diameter and tube outer diameter, the initial radial gaps, have significant effects on the minimum hydraulic expansion pressure. At the same time, the wall thickness deviation has a linear effect. By fitting the finite element analysis results, a correction coefficient of the theoretical formula is proposed. Highlights: Minimum expansion pressures increase with increasing tube wall thickness deviations. Initial radial gaps have significant effect on the minimum expansion pressure. A comprehensive deviation correction factor is given.